Joint-optimization of transportation and inventory management on a blood supply chain (2023)
Logistics is an ancient discipline defined by Don Taylor [4] as that part of the supply chain management that plans, implements, and controls efficiently and effectively forward and reverse flows and storage of goods, services, and related information between the point of origin and the point of consumption to meet customer requirements. Logistics has become a significant issue in several areas, such as industry, services, agri-food, and healthcare. This thesis deals with the healthcare sector. In this context, healthcare logistics encompasses the activities related to the numerous flows in the healthcare supply chain (HSC), which is the system composed of organizations, people, information, and resources to satisfy patient needs. The healthcare sector is a focus of governments due to its importance in society and its economic impact. In particular, global health spending represented about 10% of the gross domestic product in 2017 [5]. This sector has been attracting attention since 2015, when the UN listed good health and well-being as an sustainable development goal (SDG). One of the main challenges in the healthcare sector is that although it continues expanding more rapidly than the economy, statistics indicate that the increase in government revenues does not translate to a larger budget share for health. Indeed, global health spending grew by 3.9% a year between 2000 and 2017, while global gross domestic product grew by 3.0% [5]. However, in some cases (e.g., Vietnam and India), the share for health declined during this equivalent period, as countries used the added government revenues for other priorities [5]. This produces a broader impact on low-income countries since the distribution of global health spending is highly unequal. For low-income counties, health spending was only 41 USD a person in 2017, compared to 2937 USD in high-income countries [5].